Pengaruh Teknologi Finansial, Gaya Hidup Konsumtif, Literasi Keuangan Terhadap Pengendalian Keuangan Mahasiswa Kota Palangka Raya - Muhammad Arie Rahman; Solikah Nurwati; Iren Nita Br Barus; Yaya Meyrianisa; Nur Choerunisa; Selvia Nur Hidayah (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2025)
The development of financial technology, a consumptive lifestyle, and low financial literacy are challenges for students in managing their finances. Students as a productive age group are often unable to control their finances effectively, especially in Palangka Raya City. This study aims to analyze the influence of financial technology, a consumptive lifestyle, and financial literacy on students' financial control. The population of this study were college students in Palangka Raya City who were selected through purposive random sampling techniques. The method used was qualitative which was quantified with a multiple linear regression approach, and data processing using SPSS. The results of the study showed that the independent variables of financial technology, consumptive lifestyle, and financial literacy had a significant simultaneous effect on students' financial control. However, only financial literacy had a partial effect. This finding emphasizes the importance of increasing financial literacy and controlling consumptive behavior in the digital era. A balance between the use of financial technology and financial awareness is needed so that students are able to manage their finances wisely and independently.